2018
DOI: 10.1177/0363546517751141
|View full text |Cite
|
Sign up to set email alerts
|

Revision Anterior Cruciate Ligament Reconstruction Outcomes in Younger Patients: Medial Meniscal Pathology and High Rates of Return to Sport Are Associated With Third ACL Injuries

Abstract: Younger patients are at significant risk of having multiple ACL injuries. The high rate of third ACL injuries presents a significant issue for future knee health in these young athletes. Medial meniscal pathology and returning to high-risk sport are factors that are significantly associated with the high multiple ACL injury rate in the young.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
1
50
0
3
Order By: Relevance
“…11,13,14 Several studies identified young age as a risk factor for second ACL injuries, with injury rates in the range of 20% to 35%. [15][16][17][18] Webster et al 19 questioned whether young age in indeed a risk factor or a proxy for higher exposure to risk activity like returning to soccer or other pivoting sports. The very high rate of further ACL injuries in soccer players who return to play in our study is a further indication in support of that reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 Several studies identified young age as a risk factor for second ACL injuries, with injury rates in the range of 20% to 35%. [15][16][17][18] Webster et al 19 questioned whether young age in indeed a risk factor or a proxy for higher exposure to risk activity like returning to soccer or other pivoting sports. The very high rate of further ACL injuries in soccer players who return to play in our study is a further indication in support of that reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…This range of variability is consistent with data published for ACL reconstruction and not as high as in some series reporting outcomes of ACLR in young athletes participating in pivoting sports. [58][59][60] Comparative studies only reported graft rupture rates at shorter durations of follow-up. Although it is promising to note a lack of significant difference in graft rupture rates in the comparative studies, they were associated with a high risk of bias with respect to MINORS criteria and specific limitations included a lack of randomization, a small study population, and an absence of a sample size 50 and Henle et al, 36 do not report the rehabilitation protocol followed.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Meniscal pathology has been shown to increase the risk of poor outcomes 43 , 44 and graft rupture in the setting of revision ACL reconstruction. 30 Cartilage pathology has also been shown to worsen outcomes in this setting, with increased pain, stiffness and functional limitation. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%